Gubernaculum and Epididymo-Testicular Descent: Review of the Literature - Ivanova, Eleonora; Vincel, Beata; Verkauskas, Gilvydas; Hadziselimovic, Faruk (Acta medica Lituanica, 2022)
Cryptorchidism is a common disorder in boys that has been widely studied both experimentally and clinically. The role of the gubernaculum, a mesenchymal tissue extending from the fetal testis and epididymis to the developing scrotum, is still unclear. Even the name is debated: ‘gubernaculum epididymis’ or ‘gubernaculum testis’. This review does not aim to provide a global overview of competing theories on testicular descent, but focuses on the role of the gubernaculum in epididymo-testicular descent. We identified four major pitfalls of gubernaculum research: the role of the gubernaculum, of insulin-like peptide 3, anti-Müllerian hormone, and androgens. The major critical issues were that the gubernaculum plays a guiding role for the epididymis, descending prior to the testis and expanding the inguinal canal; insulin-like peptide 3 is not as important for the process of descent in humans as the rate of insulin-like peptide 3 mutations is low; anti-Müllerian hormone plays no significant role in epididymo-testicular descent; androgens and gonadotropins play a crucial role in epididymo-testicular descent. The role of the epididymis in the complex process of gubernaculum, epididymis, and testis migration is underestimated and should be included in future research.
Keywords: cryptorchidism; epididymo-testicular descent; gubernaculum; Insl3